The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acs.nanolett.3c00086
|View full text |Cite
|
Sign up to set email alerts
|

Single Molecule Protein Segments Sequencing by a Plasmonic Nanopore

Abstract: Obtaining sequential and conformational information on proteins is vital to understand their functions. Although the nanopore-based electrical detection can sense single molecule (SM) protein and distinguish among different amino acids, this approach still faces difficulties in slowing down protein translocation and improving ionic current signal-to-noise ratio. Here, we observe the unfolding and multistep sequential translocation of SM cytochrome c (cyt c) through a surface enhanced Raman scattering (SERS) ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…We found that the amino acid residues played an important role in the conformational change of CaM. Similar method was also utilized to study the unfolding and multistep sequential translocation of a single cytochrome c molecule through a SERS active gold plasmonic nanopore (Figure b) …”
Section: Advancements In Nanopore Sensorsmentioning
confidence: 94%
“…We found that the amino acid residues played an important role in the conformational change of CaM. Similar method was also utilized to study the unfolding and multistep sequential translocation of a single cytochrome c molecule through a SERS active gold plasmonic nanopore (Figure b) …”
Section: Advancements In Nanopore Sensorsmentioning
confidence: 94%
“…[112] As shown in Figure 11b, Ji and Wang et al combined SERS with a goldcoated nanopipette to obtain direct insight into protein segments, which shed light on nanopipette-based protein sequencing. [113]…”
Section: Optical Methodsmentioning
confidence: 99%
“…b) The schematic diagram for single molecule cyt c passing through the gold nanopore under negative bias voltage. [113] Reproduced with permission. Copyright 2023, American Chemical Society.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Integration of SERS and nanopore could directly facilitate further generation of sequencing and the development of molecular dynamic research and related fields, such as biocatalysts and drug development . However, the efficiency of plasmonic coupling of the nanopore structure are still not high enough to provide sufficient fingerprint information on molecules in the nanopore, which demands rational design of nanopore structures …”
Section: Challenges and Opportunitiesmentioning
confidence: 99%